Performing Need Analysis and Design of Training on Global Navigation Satellite System Related Applications for GRACE - Rajendranath, Arvind Subramani (2011)
The use of signals from Global Navigation Satellite Systems (GNSS) for various industrial applications has increased tremendously increased over the last ten years. With the evolution of new technologies and the launch of new satellite systems by different countries, new applications of these signals have emerged. A change in technology creates a need for training. The existing industries and new entrants need to learn and get trained to improve and sustain business performance.